Endogenous androgens and risk of epithelial invasive ovarian cancer by tumor characteristics in the European Prospective Investigation into Cancer and Nutrition. Issue 2 (16th June 2014) - Ose, Jennifer; Fortner, Renée T.; Rinaldi, Sabina; Schock, Helena; Overvad, Kim; Tjonneland, Anne; Hansen, Louise; Dossus, Laure; Fournier, Agnes; Baglietto, Laura; Romieu, Isabelle; Kuhn, Elisabetta; et al.
<x xml:space="preserve">Abstract</x> The role of endogenous androgens and sex hormone‐binding globulin (SHBG) in ovarian carcinogenesis is poorly understood. Epithelial invasive ovarian cancer (EOC) is a heterogeneous disease and there are no prospective data on endogenous androgens and EOC risk by tumor characteristics (histology, grade, stage) or the dualistic model of ovarian carcinogenesis (i.e. type I vs. type II, leading to less or more aggressive tumors). We conducted a nested case–control study in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort evaluating androgens and SHBG and invasive EOC risk by tumor characteristics. Female participants who provided a blood sample and were not using exogenous hormones at blood donation were eligible (n = 183, 257). A total of 565 eligible women developed EOC; two controls (n = 1, 097) were matched per case. We used multivariable conditional logistic regression models. We observed no association between androgens, SHBG and EOC overall. A doubling of androstenedione reduced risk of serous carcinomas by 21% (odds ratio (OR)log2 = 0.79, 95% confidence interval [CI] = [0.64–0.97]). Moreover, associations differed for low‐grade and high‐grade carcinomas, with positive associations for low‐grade and inverse associations for high‐grade carcinomas (e.g. androstenedione: low grade: ORlog2 = 1.99 [0.98–4.06]; high grade: ORlog2 = 0.75 [0.61–0.93], phet ≤ 0.01), similar associations were observed for type I/II tumors. This is the first prospective study to evaluate androgens, SHBG and EOC risk by tumor characteristics and type I/II status. Our findings support a possible role of androgens in ovarian carcinogenesis. Additional studies exploring this association are needed.